Should energy efficiency be improved? the impact of energy efficiency improvements on green economic growth—evidence from China - Wu, Lei; Zhu, Chengao; Cheng, Mengxuan; Dai, Wen; Wang, Guonian (Frontiers in Energy Research, 2023)
Green economic growth is the main direction of China’s future economic development, while energy efficiency improvement—an important prerequisite for promoting the nation’s sustainable development—is a necessary way to guarantee its economic transformation and development. It is thus of great practical significance to study the relationship between energy efficiency improvement and green economic development. On the basis of analyzing the mechanism and how energy efficiency improvement influences green economic growth, this paper measures energy efficiency with the SBM model and constructs a system of green economic growth index, and verifies the relationship between energy efficiency improvement and green economic growth with an econometric model empirical analysis. It is found that, on the whole, the improvement of energy efficiency at this stage in China inhibits green economic growth. However, with the improvement of energy efficiency level, the inhibition effect gradually weakens, showing a non-linear trajectory of “inhibition–inhibition weakening”. At present, China’s energy rebound effect is still on the rise in the short term, and green economic development is restrained to a certain extent. The current expansion of the industrial sector will exacerbate resource consumption and pollutant emissions, while technological innovation and urbanization levels will alleviate the current energy rebound tension. The paper concludes with recommendations from the perspectives of the government, R&D institutions and personnel, the power sector, and urbanization.